Drought and smut resistance of millet (Panicum miliaceum L.) seedlings - Gorlachova, O.; Gorbachova, S.; Yegorov, D.; Ansyferova, O.; Prodanyk, A.; Samborska, O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2021)
The aim of the work was to study the impact of drought on the millet (Panicum miliaceum L.) seed germination and morphological parameters of seedlings and to identify millet genotypes with balanced rhizo- and organogenesis under arid conditions. Since the soil drought weakens plant immunity during seed germination and provokes development of various diseases, especially smut (Sorosporium destruens (Schlecht) Yanki), it is necessary to identify plant genotypes with high resistance to virulent smut races. We studied resistance of 28 millet varieties to 13 smut races registered in Ukraine. The osmotic PEG 6000 (23 %) was used to simulate soil drought during the seed germination. After six days of incubation, seed germinability was assessed and the length of shoots and roots of seedlings was measured. The stress resistance of millet varieties was evaluated by the root length/shoot length ratio (R/S). Water deficit in the soil decreased seed germinability to 50.12 %. Morphological changes were more pronounced in shoots (decrease in length by 77.3 %) than in roots (decrease by 37.7 %). Under favorable weather conditions, the rhizo- and organogenesis in seedlings was even (R/S=0.75±0.02). In case of soil drought, the ratio R/S dropped to 2.19±0.03. Most of the varieties were resistant to smut races Rs 1, Rs 5–Rs 7, and Rs 9–Rs 11; in addition, around 10 % of the studied varieties was highly resistant (9–8 points) to smut races Rs 2, Rs 8, Rs 12, and Rs 13. Millet genotypes resistant to Rs 3 smut race were not found. Thus, the varieties with R/S ratio around one and higher should be considered the most valuable genetic material in selection for drought resistance. High R/S ratios were observed in the varieties Zapovitne (1.77), Zolushka (1.54), Olitan (1.4), Skado (1.79) and Danilo (1.79). The varieties Olitan and Danilo were highly resistant to the smut races Rs 1, Rs 4, Rs 7, Rs 9–Rs 11, while the varieties Novokyivske 0.1 (2.17) and Konstantynivske (2.22) to the smut races Rs 1, Rs 4–Rs 7, Rs 9–Rs 12. The variety Bila Altanka was not affected by the most virulent smut races Rs 2, Rs 8 and Rs 13. We recommend to include these millet genotypes in selection for drought and smut resistance.